2018 IEEE Southwest Symposium on Image Analysis and Interpretation (SSIAI) 2018
DOI: 10.1109/ssiai.2018.8470355
|View full text |Cite
|
Sign up to set email alerts
|

Robust Head Detection in Collaborative Learning Environments Using AM-FM Representations

Abstract: We study the problem of detecting talking activities in collaborative learning videos. Our approach uses head detection and projections of the log-magnitude of optical flow vectors to reduce the problem to a simple classification of small projection images without the need for training complex, 3-D activity classification systems. The small projection images are then easily classified using a simple majority vote of standard classifiers. For talking detection, our proposed approach is shown to significantly ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Additional references for the AM-FM theory were used from [13]. Also, regarding the Gabor filterbank with DCA, AM-FM methods has been used as a feature extraction for head and hair detection in group interactions, refer to [10] and [11].…”
Section: Am-fm Demodulationmentioning
confidence: 99%
“…Additional references for the AM-FM theory were used from [13]. Also, regarding the Gabor filterbank with DCA, AM-FM methods has been used as a feature extraction for head and hair detection in group interactions, refer to [10] and [11].…”
Section: Am-fm Demodulationmentioning
confidence: 99%
“…The current paper dramatically extends this prior research that was focused on very short video datasets without considering occlusion, appearance issues, and associating hands with different people. We also note that head detection and person recognition has been studied in [14], [15], [19] and [17]. Human activity classification over cropped regions was studied in [5], [16] and [8].…”
Section: Introductionmentioning
confidence: 99%
“…In [4], the authors introduced methods for detecting writing, typing, and talking activities using motion vectors and deep learning. In [6], the authors developed methods to detect where participants were looking at. In [7], the authors demonstrated that FM images with low-complexity neural networks can provide face detection results that can only be achieved with much more complex deep learning systems.…”
Section: Introductionmentioning
confidence: 99%